Cornstarch requirements of the adult glycogen storage disease Ia population: A retrospective review. Issue 2 (4th September 2019) - Dahlberg, Kathryn R.; Ferrecchia, Iris A.; Dambska‐Williams, Monika; Resler, Traci E.; Ross, Katalin M.; Butler, Gail L.; Kuo, Chia‐Ling; Ryan, Patrick T.; Weinstein, David A.
Abstract: Cornstarch has been the primary treatment for glycogen storage disease type Ia (GSD Ia) for over 35 years. When cornstarch was first described as a treatment, few people survived beyond early childhood. As the prognosis for this population has improved, the need to ensure appropriate cornstarch dosing for different age groups has become imperative. Records from 115 patients (10‐62 years of age) with GSD Ia evaluated at our center between 2015 and 2017 were reviewed. Data collected included weight, age, genetic mutation, amount and frequency of cornstarch doses, body mass index, gender, 24‐hour glucose and lactate concentrations, and biochemical markers of metabolic control. The data demonstrate that adult treatment needs vary greatly from younger age groups, and the required cornstarch support decreases with age ( P < .001). The required number of doses, however, did not change with a mean of six doses (range 4‐8) daily in all age groups. General laboratory findings across time demonstrate that significantly reducing the amount of starch required to maintain euglycemia with aging can be done without sacrificing metabolic control. Carbohydrate requirements decrease with aging, and older patients were found to require less cornstarch. Failure to lower the cornstarch doses contributes to over‐treatment in adults with GSD Ia. Not only does this lead to worsening hepatomegaly and excessive weight gain, but over‐treatment contributes to relative hyperinsulinism and rebound hypoglycemia. This knowledge is essential in designing nutritional therapies for the aging GSD population.